EFEKTIFITAS MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PENINGKATAN MINAT BELAJAR SISWA DI MTs NURUL IMAN JOMBANG - Nurul Indana; Khusnul Azizah (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2021)
Contextual Teaching and Learning (CTL) model is a learning model that links subject matter with real-life contexts that can provide meaning for students and make students more active, so as to increase student interest in learning. The research method used in this study is a qualitative research method with a qualitative descriptive research design. Data collection techniques using interview techniques, observation, and documentation. Furthermore, data analysis was carried out using the stages of data reduction techniques, data display, and data verification. The results of this study indicate that: The steps of the CTL model, namely students construct their own knowledge, inquiry, ask questions, form a learning community, modeling, reflection, and real assessment. The most important goal of the CTL model is that students can find the meaning of the subject matter so that it can be practiced in students' lives and used as a means of worshiping the Almighty. The four indicators of student interest in learning have been fulfilled including: feelings of pleasure, student involvement, and student attention. Supporting factors include: students' interest in learning is high, stable and easy to talk to, friends, students' closeness to teachers. While the inhibiting factors include: lack of support from the family, students come from broken homes and lack of support.